Distribution of dense bone island in the jaw based on the classification of radiopaque areas and their location on panoramic radiographs - Yunita Savitri; Eha Renwi Astuti; Aga Satria Nurrachman; Sri Wigati Mardi Mulyani; Dina Karimah Putri; Diana Lilik Zainiyyah; Hilda Majidah (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2022)
Objectives: This study is aimed to find out the distribution of DBI in the jaw based on the classification of radiopaque areas and their location using panoramic radiographs at RSKGMP Universitas Airlangga Surabaya. Materials and Methods: This research was a descriptive observational study with total sampling method. The study used secondary data from panoramic radiographs at the RSKGMP Airlangga University Surabaya during 2018–2021, which had a DBI appearance, and analyzed them based on the classification of radiopaque areas and locations. The results of the analysis are then presented in the form of tables and pie charts. Results: Classification of DBI based on radiopaque areas was found in type 5 separate (47.81%), type 4 apical (29.82%), type 3 apical and interradicular (17.54%), type 1 interradicular (3.07%), and the least in type 2 interradicular and separate (1.75%). The most common locations of the lesions were in the premolar region (42.54%), the molar region (27.63%), the canine region (12.28%), the canine-premolar region (8.33%), the premolar-molar region (6.58%), and the least common location in the incisor and incisor-canine regions (1,32%). Conclusion: Classification of DBI based on the most common radiopaque area was found to be type 5 separate, with the most lesion locations in the premolar region. While the least classification was found in type 2 interradicular and separate, the incisive and incisive-canine regions had the fewest lesion locations.